Pelatihan Pembuatan Rencana Usaha pada Pedagang di Sekitar Obyek Wisata Benang Stokel, Desa Aikberik, Kecamatan Batukeliang Utara, Lombok Tengah - Alamsyah AB; Suprianto; Sagir, Junaidi; Saufi, Ahmad; Abidin, Zainal; Manan, Abdul (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
This service has the theme of Training in Making Work Plans for Traders around the Benang Stokel tourist attraction, Aikberik village, North Batukeliang subdistrict, Central Lombok. The extension activity was carried out on July 27 2022 with the delivery of material for 30 minutes by the service team, then continued with discussions and training in making work plans for training participants who were generally traders. All participants responded very well to the material presented and the participants were very interested in practicing the knowledge taught, especially in terms of the need to carry out business planning in the form of written documents as a guide and evaluation of the activities carried out. With the material and knowledge obtained, it can be used as a guide for carrying out business activities, so that with the implementation of this plan in the future it can increase community income in the Benang Stokel tourist area of ​​Aikebrik village. This training in making a Business Plan can open minds and perspectives regarding business management which has been run very traditionally to better business management/management which can support the success of their business, especially in terms of marketing, production, human resources and marketing activities. It is hoped that in the future this outreach activity can continue in the form of business training for traders in the Benang Stukel tourist area.